Quantitative ethnoveterinary study on plant resource utilization by indigenous communities in high-altitude regions - Haq, Shiekh Marifatul; Yaqoob, Umer; Majeed, Muhammad; Amjad, Muhammad Shoaib; Hassan, Musheerul; Ahmad, Riyaz; Waheed, Muhammad; Bussmann, Rainer Willi; Calixto, Eduardo Soares; Proćków, Jarosław; de la Lastra, José M. Pérez; Morales-de la Nuez, Antonio (Frontiers in Veterinary Science, 2022)
For millennia, ethnic knowledge has been intricately linked to local biodiversity and has been imprinted in the fabric of rural communities. Growing scientific evidence suggests that merging ethnic knowledge with new scientific findings can lead to socially acceptable and environment friendly approaches that are essential for the long-term prosperity of local communities. In the high-altitude region, where livestock raising is a key source of revenue, plant-based utilization for ethno-veterinary practice is commonly employed. In this context present study was conducted with the aim to document the ethno-veterinary use of plant resources in different bio-geographic regions of Jammu and Kashmir’s Himalayas (J&KH). Semi-structured interviews and group discussions were used to collect information. Principal component analysis (PCA) and Pearson correlation was done to analyze the data. We documented 148 species belonging to 53 families used as medicine, fodder, tonic, antidote, magic, and also against the ectoparasite by the inhabitants this region. There were significant differences in the relative usage of plant resources across the three biogeographic regions. Comparatively, highest number (41%) of plant species were used for ethnoveterinary in Jammu region, while lowest number (28%) species were used in Kashmir. Across the regions, Kashmir and Jammu had the highest level of species similarity (17%), while Jammu and Ladakh had the lowest (1%). A cross-regional assessment of plant resources revealed that 18% of plants overlapped between the regions. The reported use of Amaranthus blitum, Morus alba, Ficus palmata, Vitex negundo, Juniperus semiglobosa, Ulmus wallichiana, Rumex nepalensis are novel for the ethno-veterinary uses to this part of the Himalayan region. The various dry unique fodder preparations (gaas lov, gass khor, pan baath, kaand baath, Lov gooad, Karb, Phungma) from plant resources are reported for the first time from the Himalayan region and can be ascribed as the novelty of the present study. Plant resources were not only a source of fodder and medicine but also an opportunity for livelihood generation. Our findings bridge the knowledge gap by documenting key ethnoveterinary applications of native plant species from the study region used to cure livestock diseases and disorders by the mountain inhabitants.